Does loneliness mediate the relationship between support and depressive symptoms among University Students during COVID-19 pandemic? - Aníta Ýr Hrafnsdóttir 1995- (2022)
There were significant changes worldwide with the advent of the pandemic, COVID-19. Along with these changes, has the impact of COVID-19 on mental health generated a lot of interest among researchers. Recent studies have shown that depression and loneliness increased among individuals, during COVID-19 particularly among university students. Studies have also established the importance for university student to receive support from both family and friends, to get through pandemic times. The current study´s aims were to investigate the impact of support on loneliness and depression among university students in Iceland during the pandemic. The current study was a part of a larger on-going study among university students at Reykjavik University about how student´s health changed during COVID-19. The participants were university students at Reykjavik University (N = 654), 383 females (58.6%), 270 males (41.3%), and 1 another (0.2%), ranging from age 18–49 years. Mediation analysis was performed to explore the possible underlying mechanism of how support influences depression through loneliness. The findings showed that increased support was significantly associated with decreased loneliness, and that increased loneliness was associated with decreased depression. Further, increased support was associated with decreased depression. In total, results indicated that total support had a significant increasing effect on depression through loneliness. Keywords: depression, loneliness, support, university students, COVID-19. Gríðarlegar breytingar urðu um allan heim með tilkomu heimsfaraldursins, COVID-19. Auk þessara breytinga, varð mikil aukning meðal vísindamanna um áhrif andlegrar heilsu af völdum COVID-19 meðal almennings. Nýlegar rannsóknir hafa sýnt fram á að þunglyndi og einmannaleiki jókst meðal einstaklinga, þá sérstaklega á meðal háskólanema á tímum heimsfaraldursins. Rannsóknir hafa einnig sýnt fram á hversu mikilvægur stuðningur frá bæði fjölskyldu og vinum er fyrir háskólanema til að takast á við þessar ...